Kehadiran Rayap dan Tanda-Tanda Infestasinya pada Bangunan Rumah Di Kawasan ‘Kebun Karet’ Gundaling, Tamiang Layang, Barito Timur, Kalimantan Tengah - Eva Oktoberyani Christy; Yosefin Ari Silvianingsih (HUTAN TROPIKA, 2023)
Land clearing carried out in part or all of the ‘Rubber Garden’ area for settlement often leave stumps and branches that becomes food sources for termites and when the food sources is ran out, termites attack extends to the wooden structure of the house building and becomes a destructive pest. The aim of this research was to detect the presence of termites through signs of infestation on house building and yard located in the Gundaling ‘Rubber Garden’, Barito Timur Regency. Twenty house buildings were observed. Visual detection of termite infestation signs was conducted on house building and yard such as on wooden building components, fuel wood, stump, dead and living trees, and recording wooden building components damaged by termite infestation. Termites specimens were collected by directly capture termites from mud tubes and nests on the observed house buildings and yards. The results showed the presence of termites from the genus Nasutitermes on house buildings through signs of infestation in the form of mud tubes, carton nests, and damaged wooden building components. In the yard, the genus Nasutitermes was found through signs of infestation in the form of a mud tubes, arboreal carton nest, while the signs of termite infestation of genus Coptotermes was in the form of shelter tubes.